How the EndNote Gives Accurate In-Text Citations in Academic Writing - Sharma, Uma Nath (Access: An International Journal of Nepal Library Association, 2023)
End Note is a reference management software programme among many others—such as Mendeley, Ref Works, and Zotero—for storing, managing, retrieving, and using sources for citation in an academic writing. This phenomenological study deals with how the use of the software gives accurate in-text citations of all types of references, such as, books, book sections, theses, journal articles, WebPages, and newspaper articles with reference to APA 7th style of academic writing. For this, I draw reflections on my own direct experience of using End Note for the purpose of citation as a practitioner, tutor, and trainer during the last four years. I categorize the in-text citations into themes on the basis of the way they can be accurately managed in MS (Microsoft) word file, and describe how to enter the input so that the resultant output gives accurate in-text citation with special reference to APA 7th. Drawing on the findings, I have concluded that the use of End Note helps to accurately and systematically manage the citation with very little manual adjustment, and thereby to accelerate and systematize the academic writing as a whole.